Angiofibroma of soft tissue with fibrohistiocytic features and intratumor genetic heterogeneity of NCOA2 gene rearrangement revealed by chromogenic in situ hybridization: A case report. (May 2014) - Fukuda, Yumiko; Motoi, Toru; Kato, Ikuma; Ikegami, Masachika; Funata, Nobuaki; Ohtomo, Rie; Horiguchi, Shinichiro; Goto, Takahiro; Hishima, Tsunekazu
<x xml:space="preserve">Abstract</x> Angiofibroma of soft tissue is a recently described soft tissue tumor that is characterized by fibroblastic spindle tumor cells with arborizing capillary proliferation. Cytogenetically, it harbors a specific fusion gene involving the nuclear receptor coactivator 2 (NCOA2) gene. We report here additional new pathological and cytogenetic features. A soft tissue tumor in the left thigh of 73‐year‐old female was investigated. Microscopically, histiocytoid tumor cells were scattered in an edematous background with branching capillary proliferation. Immunohistochemically, we identified that the tumor cells were positive for histiocytic markers such as CD68 and CD163. Rearrangement of the NCOA2 gene was detected successfully by chromogenic in situ hybridization; however, abnormal signal patterns were observed in only a small subset of tumor cells. Unlike typical tumors with bland spindle cells, the present tumor needs to be distinguished from myxoid, dendritic and clear cell tumors. This case may suggest that angiofibroma of soft tissue is not in the center of the fibroblastic/myofibroblastic tumor group, but rather shows a fibrohistiocytic nature. We also found intratumor genetic heterogeneity, which is uncommon for a translocation‐associated tumor. Therefore, careful evaluation is required to detect the gene rearrangement in this tumor entity.